دراسة تأثير الأكاروس Tetranychus urticae Koch في إنتاج الفريز بوجود المفترس Phytoseiulus persimilis Athias-Henroit تحت ظروف الزراعة المحمية - زيدان, رياض; حلوم, منذر; شعبو, أليسار (Latakia University Journal -Biological Sciences Series, 2018)
تمت دراسة أثر إصابة نباتات الفريز( الصنف Oso Grande) بالأكاروس Koch Tetranychus urticae في نسبة العقد، وكمية الإنتاج، ووزن وقطر الثمار بوجود المفترس الأكاروسي Phytoseiulus persimilisAthias-Henriot تحت ظروف الزراعة المحمية. وأظهرت النتائج تفوق معاملتي الشاهد والمفترس معنوياً على معاملة الفريسة من حيث نسبة العقد إذ بلغت31 % لمعاملة الفريسة، مقابل 46 % للشاهد، و41 % للمفترس، في حين بلغت كمية الإنتاج 2807، 2715 غ/م2 للشاهد والمفترس بالترتيب مقابل 1591 غ/م2 لمعاملة الفريسة. تبين أيضاً عدم وجود فروق معنوية في قطر ثمار الفريز، في حين أدّت إصابة نباتات الفريز إلى زيادة تشوه الثمار مما أدى إلى انخفاض نسبة الثمار القياسية حيث بلغت 99.6، 88، 98 % للمعاملات شاهد، فريسة، مفترس بالترتيب. This research was carried out to study the effect of Tetranychus urticae infection of strawberry plants variety (oso grandi) on the fruiting rate, the yield, the fruit weight and diameter in the presence of the predatory mite Phytoseiulus persimilis under green house conditions. Results of statistical analysis showed that the control and predator treatments were significantly the best where the fruiting rate reached 31% in the prey treatment; while it was 46% for control and 41% for predator. The quantity of production was 2807 2715 g/ m2 for control and predator, while it was 1591g/ m2 in the prey treatment. Significant differences between the treatments in the fruit diameters were noticed, while the infection increased fruit deformation and led to a decrease of the percentage of standard fruits, which reached 99.6, 88, 98% in the control, prey, and predator treatments continuously.